Graphene capsule fused salt phase change material as well as preparation method and application thereof
By using a combination method of a small layer of graphene oxide, polyvinyl alcohol and sodium ascorbate in graphene-based molten salt phase change material, the long-term stability and integrated compatibility of the material are solved. The combination of high thermal conductivity and high latent heat storage capacity is achieved, and is suitable for energy storage and thermal management applications.
Patent Information
- Application Number
- CN202411301107.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The long-term stability of existing graphene-based molten salt phase change materials is poor and the integration compatibility with existing systems is poor, limiting their practical application.
A small layer of graphene oxide, polyvinyl alcohol and sodium ascorbate are mixed to form a slurry, poured into the mold to fill the molten salt and pressurized to form a tightly coated precursor. After freeze-drying, it is calcined at high temperature to obtain ceramicized graphite An ene capsule molten salt phase change material, combining the high thermal conductivity of graphene and the high latent heat storage capacity of molten salt.
It significantly improves the thermal management and storage performance of phase change materials, improves mechanical strength and thermal stability, has high thermal conductivity of the material and is not easy to leak molten salts, and has high long-term stability. It is suitable for energy storage devices and energy storage systems.
Smart Images

Figure CN119220229A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of molten salt phase change materials, and in particular to a graphene capsule molten salt phase change material and a preparation method and application thereof. Background Art
[0002] With the continuous development of global science and technology and industry, the demand for efficient and reliable new functional materials is growing. In many key fields such as energy storage, environmental purification, electronic equipment and metal smelting and processing industries, the application of high-performance energy storage materials has become the key to improving efficiency and achieving technological breakthroughs. As a new type of energy storage material, graphene-enhanced molten salt phase change material has gradually become a hot spot for research and industrial applications due to its unique physical and chemical properties.
[0003] Graphene-based molten salt phase change materials combine the high thermal conductivity of graphene with the high latent heat storage capacity of molten salt, providing a solution that can maintain excellent thermal performance even in extreme environments. The high thermal conductivity of graphene significantly improves the thermal response speed and thermal management capabilities of phase change materials, while the high latent heat of molten salt enhances its thermal energy storage efficiency. Zhang et al. found that by introducing graphene into phase change materials, their thermal conductivity and stability can be significantly improved, making them widely used in solar thermal energy storage, building heating and cooling systems. In addition, this composite material also shows excellent thermal cycle stability and can maintain high thermal energy storage and release efficiency in multiple thermal cycles. Li et al. studied graphene-enhanced phase change materials, demonstrating their improved thermal properties and their potential in advanced energy storage systems. Kim et al. developed a capsule phase change material based on graphene powder embedding, demonstrating its potential for application in smart and flexible thermal response. In addition, Li et al. studied the thermal properties of composite phase change materials containing palmitic acid / bentonite / graphene, providing new options for thermal energy storage.
[0004] However, despite the excellent performance of graphene-based molten salt phase change energy storage materials in theory, their practical application still faces some challenges, such as poor long-term stability and poor integration compatibility with existing systems. It is urgent to develop new graphene-based molten salt phase change materials. Summary of the invention
[0005] The present application provides a graphene capsule molten salt phase change material and a preparation method and application thereof, aiming to solve the problems of poor long-term stability and poor integration compatibility with existing systems existing in existing graphene-based molten salt phase change materials.
[0006] In order to achieve the above objectives, the present application adopts the following technical solutions.
[0007] In a first aspect of the present application, a method for preparing a graphene capsule molten salt phase change material is provided, comprising:
[0008] S1, dispersing few-layer graphene oxide, polyvinyl alcohol and sodium ascorbate in water, heating and stirring to obtain a uniform slurry;
[0009] S2, adding the slurry into a mold, filling the solar salt to the center of the slurry, applying pressure to the mold so that the slurry tightly covers the solar salt, and freeze-drying to obtain a capsule precursor;
[0010] S3, calcining the capsule precursor for the first time in an inert atmosphere, and then heating it for the second time to obtain a graphene capsule molten salt phase change material.
[0011] In some embodiments, the few-layer graphene oxide is prepared by the following method:
[0012] Mix graphite and sulfuric acid evenly, add sodium nitrate and phosphorus pentoxide, stir at 80-100°C for 12-24h, separate and collect the solid phase, wash and shade-dry to obtain the precursor;
[0013] The precursor is dispersed in excess concentrated sulfuric acid, and potassium permanganate is slowly added thereto, stirred at -10 to 0°C, and then diluted with water, and then heated to 90°C, and hydrogen peroxide is added until the solution turns bright yellow to obtain a dispersion;
[0014] The dispersion is diluted with water, centrifuged at a speed of 5000-7000 r / min to remove multilayer graphene oxide, and then centrifuged at a speed of 10000-12000 r / min to remove impurities, and the concentrated solution obtained by centrifugation is freeze-dried to obtain few-layer graphene oxide.
[0015] In some embodiments, the mass ratio of graphite, sulfuric acid, sodium nitrate and phosphorus pentoxide is (1-2):(18-20):(1.5-2):(1.5-2);
[0016] The mass ratio of potassium permanganate to graphite is 5:1.
[0017] In some embodiments, the heating temperature is 80° C.; the mass of the few-layer graphene oxide in the slurry is 10-20 mg / mL, the concentration of polyvinyl alcohol is 120-180 mg / mL, and the concentration of sodium ascorbate is 0.3-0.8 mg / mL.
[0018] In some embodiments, the solar salt is prepared by the following method: NaNO3 and KNO3 are mixed in a mass ratio of 6:4, ground and heated to 400°C to melt, cooled and ground again to obtain solar salt.
[0019] In some embodiments, the diameter of the mold is 1 to 3 cm, and the pressure applied to the mold is 10 to 15 MPa.
[0020] In some embodiments, the freeze-drying comprises:
[0021] The mold is frozen by liquid nitrogen for 10 to 12 hours; then dried for 24 to 48 hours at a temperature of -70 to -80°C and a vacuum degree of <15Pa.
[0022] In some embodiments, the temperature of the first calcination is 250-400°C; the temperature of the second calcination is 500-800°C;
[0023] The inert atmosphere is an argon atmosphere.
[0024] The second aspect of the present application provides a graphene capsule molten salt phase change material prepared by the above preparation method.
[0025] The third aspect of the present application provides the use of the graphene capsule molten salt phase change material prepared by the above preparation method in an energy storage device or energy storage system.
[0026] Compared with the prior art, the beneficial effects of this application are:
[0027] The present application forms a slurry by mixing a few-layer graphene oxide, polyvinyl alcohol and sodium ascorbate, pouring the slurry into a steel mold, filling and pressurizing molten salt to form a tightly coated precursor, and after freeze-drying, calcining at a high temperature to complete the thermal reduction of graphene and the crystallization process of molten salt, and finally obtaining a ceramicized graphene capsule molten salt phase change material with high mechanical strength and thermal stability. The molten salt phase change material is coated with graphene aerogel, has high thermal conductivity, is not easy to leak molten salt, and has high long-term stability.
[0028] The graphene capsule molten salt phase change material of the present application combines the high thermal conductivity of graphene and the high latent heat storage capacity of molten salt, significantly improves the thermal management and storage performance of the phase change material, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 This is a scanning electron microscope image of graphene capsule molten salt phase change material;
[0031] Figure 2 This is the XRD pattern of graphene capsule molten salt phase change material;
[0032] Figure 3This is the DSC test result diagram of graphene capsule molten salt phase change material;
[0033] Figure 4 This is the thermal conductivity test result of graphene capsule molten salt phase change material. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0035] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.
[0036] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0037] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0038] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0039] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0040] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0041] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] In the first aspect, the present application provides a method for preparing a graphene capsule molten salt phase change material, by mixing a few-layer graphene oxide, polyvinyl alcohol and sodium ascorbate to form a slurry, pouring the slurry into a steel mold, filling the molten salt and pressurizing to form a tightly coated precursor, and after freeze-drying, calcining at a high temperature to complete the thermal reduction of graphene and the crystallization process of the molten salt, and finally obtaining a ceramicized graphene capsule molten salt phase change material with high mechanical strength and thermal stability, specifically comprising:
[0043] S1, dispersing few-layer graphene oxide, polyvinyl alcohol and sodium ascorbate in water, heating and stirring to obtain a uniform slurry;
[0044] In the present application, few-layer graphene oxide, polyvinyl alcohol and sodium ascorbate are dispersed in water and stirred at 80° C. for 24 to 48 hours to form a uniform slurry. The slurry should be in a uniform and stable suspension state with high viscosity and a consistent dark appearance.
[0045] Wherein, the mass of few-layer graphene oxide in the slurry is 10-20 mg / mL, the concentration of polyvinyl alcohol is 120-180 mg / mL, and the concentration of sodium ascorbate is 0.3-0.8 mg / mL. Wherein, the polyvinyl alcohol is used to replace water as the main solvent, which melts at 80°C. The molten polyvinyl alcohol can effectively prevent the stratification of salt and graphene oxide and significantly improve the viscosity of the resulting slurry. In addition, the solidification temperature of polyvinyl alcohol is high and the speed is fast, which can ensure that the capsules formed in the mold have good mechanical strength and provide support before the reduction of graphene oxide. The sodium ascorbate is used to reduce the few-layer graphene oxide to obtain conductive graphene nanosheets.
[0046] S2, adding the slurry into a mold, filling the solar salt to the center of the slurry, applying pressure to the mold so that the slurry tightly covers the solar salt, and freeze-drying to obtain a precursor capsule;
[0047] In the present application, the solar salt is prepared by the following method: NaNO3 and KNO3 are mixed in a mass ratio of 6:4, ground and heated to 400°C to melt, cooled and ground again to obtain solar salt.
[0048] In the present application, the mold is preferably a cylinder with a diameter of 1-3 cm. After the slurry is added to the mold, the solar salt is pressed to the center of the slurry in the mold, and a pressure of 10 to 15 MPa is applied to the mold so that the slurry tightly covers the solar salt. The mold is then frozen with liquid nitrogen for 10 to 12 hours, and then dried for 24 to 48 hours at a temperature of -70 to -80°C and a vacuum degree of <15 Pa to obtain a coated capsule precursor.
[0049] S3, calcining the capsule precursor for the first time in an inert atmosphere, and then heating it for the second time to obtain a graphene capsule molten salt phase change material.
[0050] In the present application, the inert atmosphere is preferably an argon atmosphere, and both calcinations are performed in an argon atmosphere. The temperature of the first calcination is preferably 250-400°C to remove the polyethylene glycol in the capsule precursor; the temperature of the second calcination is 500-800°C to thermally reduce the graphene, crystallize the solar salt after melting, and enhance the mechanical strength and stability of the material, thereby obtaining a graphene capsule molten salt phase change material with a molten salt phase change material as the inner core and graphene as the outer layer.
[0051] In the present application, the few-layer graphene oxide is prepared by the following method:
[0052] Mix graphite and sulfuric acid evenly, add sodium nitrate and phosphorus pentoxide, stir at 80-100°C for 12-24h, separate and collect the solid phase, wash and dry in the shade to obtain a precursor; wherein the mass ratio of the graphite, sulfuric acid, sodium nitrate and phosphorus pentoxide is preferably (1-2):(18-20):(1.5-2):(1.5-2).
[0053] The precursor is dispersed in excess concentrated sulfuric acid, and potassium permanganate is slowly added thereto, stirred at -10 to 0°C, and then diluted with water, and then heated to 90°C, and hydrogen peroxide is added until the solution turns bright yellow to obtain a dispersion; the mass ratio of potassium permanganate to graphite is 5:1.
[0054] The dispersion is diluted with water, centrifuged at a speed of 5000-7000 r / min to remove multilayer graphene oxide, and then centrifuged at a speed of 10000-12000 r / min to remove impurities, and the concentrated solution obtained by centrifugation is freeze-dried to obtain few-layer graphene oxide.
[0055] The graphene capsule molten salt phase change material prepared in this application is coated with graphene aerogel, has high thermal conductivity, and the molten salt is not easy to leak, and has high long-term stability. It combines the high thermal conductivity of graphene and the high latent heat storage capacity of molten salt, significantly improving the thermal management and storage performance of the phase change material, and can be used in energy storage devices or energy storage systems, and applied to thermal energy storage and conversion systems, building energy conservation, electronic device thermal management, and environmental temperature control.
[0056] The present application is further described below by way of examples.
[0057] In the embodiment of the present application, solar salt is prepared by the following method: NaNO3 and KNO3 are mixed in a mass ratio of 6:4, and ground in a ball mill at a speed of 500 rpm for 60 minutes to obtain a mixed salt powder. The mixed salt powder is heated to 400°C to melt, then cooled at a cooling rate of 5°C / min, and ground again to obtain solar salt.
[0058] Example 1
[0059] This embodiment provides a method for preparing a graphene capsule molten salt phase change material, comprising:
[0060] S1, preparation of few-layer graphene oxide: 2g of flake graphite was mixed with 10ml of sulfuric acid, stirred at 80°C, and then 1.7g of sodium nitrate and 1.7g of phosphorus pentoxide were added in sequence, and stirring was continued for 12 hours; the mixture was filtered twice and dried in the shade at room temperature for 3 hours to obtain a precursor; 80ml of sulfuric acid was added to a beaker, and the precursor was added, and 10g of potassium permanganate was slowly added to the beaker at -10°C, stirred for 4.5 hours, and then treated in a 35°C water bath for 4 hours, and diluted in 1000ml of water, stirred for 15 minutes; the temperature was raised to 90°C, and hydrogen peroxide was added until the solution turned bright yellow to obtain a dispersion; the dispersion was centrifuged at a speed of 11000r / min for 7min, and then centrifuged at a speed of 6000r / min for 5min to remove impurities, and centrifuged again at a speed of 11000r / min for 15min to obtain a concentrate. The concentrate was freeze-dried for 48 hours to obtain few-layer graphene oxide.
[0061] Dissolve the few-layer graphene oxide, polyvinyl alcohol, and sodium ascorbate in water to prepare a mixed solution with a few-layer graphene oxide mass of 20 mg / mL, a polyvinyl alcohol concentration of 180 mg / mL, and a sodium ascorbate concentration of 0.8 mg / mL, and stir at 80° C. for 48 hours to obtain a uniform slurry;
[0062] S2, pour the slurry into a stainless steel mold with a diameter of 3 cm, fill the solar salt to the center of the slurry in the mold, and apply a pressure of 15 MPa to the mold to make the slurry tightly coated. Use liquid nitrogen to freeze the mold for 12 hours. After freezing, put the mold into a freeze dryer, set the temperature to -70°C, the vacuum degree <15Pa, and dry it for 48 hours to obtain a capsule precursor;
[0063] S3, heating the capsule precursor at 250°C for 2h in an argon atmosphere to remove polyvinyl alcohol; then heating to 500°C for 2h and then cooling to thermally reduce the graphene, and the solar salt melts and crystallizes to obtain a graphene capsule molten salt phase change material.
[0064] Example 2
[0065] This embodiment provides a method for preparing a graphene capsule molten salt phase change material, comprising:
[0066] S1, preparation of few-layer graphene oxide: 2g of flake graphite was mixed with 10ml of sulfuric acid, stirred at 80°C, and then 1.7g of sodium nitrate and 1.7g of phosphorus pentoxide were added in sequence, and stirring was continued for 12 hours; the mixture was filtered twice and dried in the shade at room temperature for 3 hours to obtain a precursor; 80ml of sulfuric acid was added to a beaker, and the precursor was added, and 10g of potassium permanganate was slowly added to the beaker at -10°C, stirred for 4.5 hours, and then treated in a 35°C water bath for 4 hours, and diluted in 1000ml of water, stirred for 15 minutes; the temperature was raised to 90°C and hydrogen peroxide was added until the solution turned bright yellow to obtain a dispersion; the dispersion was centrifuged at a speed of 10000r / min for 7min, and then centrifuged at a speed of 6000r / min for 5min to remove impurities, and centrifuged again at a speed of 10000r / min for 15min to obtain a concentrate. The concentrate was freeze-dried for 48 hours to obtain a few-layer graphene oxide.
[0067] Dissolve the few-layer graphene oxide, polyvinyl alcohol, and sodium ascorbate in water to prepare a mixed solution with a few-layer graphene oxide mass of 15 mg / mL, a polyvinyl alcohol concentration of 150 mg / mL, and a sodium ascorbate concentration of 0.5 mg / mL, and stir at 80° C. for 48 hours to obtain a uniform slurry;
[0068] S2, pour the slurry into a stainless steel mold with a diameter of 2 cm, fill the solar salt to the center of the slurry in the mold, and apply a pressure of 10 MPa to the mold to make the slurry tightly coated. Use liquid nitrogen to freeze the mold for 12 hours. After freezing, put the mold into a freeze dryer, set the temperature to -70°C, the vacuum degree <15Pa, and dry it for 24 hours to obtain a capsule precursor;
[0069] S3, heating the capsule precursor at 400°C for 2h in an argon atmosphere to remove polyvinyl alcohol; then heating to 800°C and heating for 2h and then cooling to thermally reduce the graphene, and the solar salt melts and crystallizes to obtain a graphene capsule molten salt phase change material.
[0070] Example 3
[0071] This embodiment provides a method for preparing a graphene capsule molten salt phase change material, comprising:
[0072] S1, preparation of few-layer graphene oxide: 2g of flake graphite was mixed with 10ml of sulfuric acid, stirred at 80°C, and then 1.7g of sodium nitrate and 1.7g of phosphorus pentoxide were added in sequence, and stirring was continued for 12 hours; the mixture was filtered twice and dried in the shade at room temperature for 3 hours to obtain a precursor; 80ml of sulfuric acid was added to a beaker, and the precursor was added, and 10g of potassium permanganate was slowly added to the beaker at -10°C, stirred for 4.5 hours, and then treated in a 35°C water bath for 4 hours, and diluted in 1000ml of water, stirred for 15 minutes; the temperature was raised to 90°C and hydrogen peroxide was added until the solution turned bright yellow to obtain a dispersion; the dispersion was centrifuged at a speed of 10000r / min for 7min, and then centrifuged at a speed of 6000r / min for 5min to remove impurities, and centrifuged again at a speed of 10000r / min for 15min to obtain a concentrate. The concentrate was freeze-dried for 48 hours to obtain a few-layer graphene oxide.
[0073] Dissolve the few-layer graphene oxide, polyvinyl alcohol, and sodium ascorbate in water to prepare a mixed solution with a few-layer graphene oxide mass of 10 mg / mL, a polyvinyl alcohol concentration of 120 mg / mL, and a sodium ascorbate concentration of 0.3 mg / mL, and stir at 80° C. for 24 hours to obtain a uniform slurry;
[0074] S2, pour the slurry into a stainless steel mold with a diameter of 1 cm, fill the solar salt to the center of the slurry in the mold, and apply a pressure of 15MPa to the mold to make the slurry tightly coated. Use liquid nitrogen to freeze the mold for 12 hours. After freezing, put the mold into a freeze dryer, set the temperature to -70℃, the vacuum degree <15Pa, and dry it for 24 hours to obtain a capsule precursor;
[0075] S3, heating the capsule precursor at 300°C for 2h in an argon atmosphere to remove polyvinyl alcohol; then heating to 600°C and heating for 2h and then cooling to thermally reduce the graphene, and the solar salt melts and crystallizes to obtain a graphene capsule molten salt phase change material.
[0076] The performance of the graphene capsule molten salt phase change material prepared in Example 1 was evaluated. Figure 1 This is a scanning electron microscope image of graphene capsule molten salt phase change material. Figure 1 It can be seen that the crystal structure is complete and evenly distributed, with a high degree of crystallinity, showing excellent uniformity, proving that the eutectic salt and graphene oxide have achieved good combination.
[0077] Figure 2 This is the XRD diagram of graphene capsule molten salt phase change material. Figure 2 It can be seen that it has obvious crystallization peaks, indicating that a good crystal structure is formed between the graphene capsule and the molten salt. The appearance of these characteristic peaks indicates the effective loading and interaction between the eutectic salt and graphene oxide, indicating that the prepared composite material has high crystallinity and stable structure.
[0078] Figure 3 This is the DSC (differential scanning calorimetry) test result of graphene capsule molten salt phase change material. Figure 3 It can be seen that the graphene capsule molten salt phase change material has excellent energy absorption and release capabilities in the thermal process, has good energy storage performance, and can stably store and release energy during temperature changes.
[0079] The thermal conductivity of the graphene aerogel, eutectic salt and molten salt phase change energy storage material prepared in Example 1 was tested by a laser flash method, specifically including:
[0080] 1. Prepare samples: Cut and prepare samples, which are square slices.
[0081] 2. Install the sample: Fix the sample in the test equipment, making sure the sample surface is flat and in good contact with the equipment.
[0082] 3. Laser irradiation: Use short pulse laser to irradiate one side of the sample.
[0083] 4. Temperature measurement: Record the temperature response on the other side of the sample, usually using an infrared sensor.
[0084] 5. Data analysis: Calculate the thermal diffusion coefficient through the temperature response curve of the sample, and then calculate the thermal conductivity based on the density and specific heat capacity of the sample.
[0085] The test results are as follows Figure 4 As shown. Figure 4It can be seen that the thermal conductivity of the graphene capsule molten salt phase change material is 0.68W / m·K, which is significantly higher than that of the single graphene aerogel (0.12W / m·K) and close to the thermal conductivity of solar salt (0.81W / m·K). This shows that the graphene capsule molten salt phase change material, although the molten salt phase change material is coated with graphene aerogel, still has high thermal conductivity; and under the protection of the graphene capsule, the molten salt phase change material is not easy to leak and has high long-term stability. The graphene capsule molten salt phase change material of this application takes into account both high thermal conductivity and long-term stability, significantly improves the thermal management and storage performance of the phase change material in the energy storage scenario, and has broad application prospects.
[0086] The same test was performed on the graphene capsule molten salt phase change materials of Example 2 and Example 3, and their structures and thermal conductivities were similar to those of the graphene capsule molten salt phase change material of Example 1.
[0087] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.
Claims
1. A method for preparing a graphene capsule molten salt phase change material, characterized in that: include: S1, dispersing few-layer graphene oxide, polyvinyl alcohol and sodium ascorbate in water, heating and stirring to obtain a uniform slurry; S2, adding the slurry into a mold, filling the solar salt to the center of the slurry, applying pressure to the mold so that the slurry tightly covers the solar salt, and freeze-drying to obtain a capsule precursor; S3, calcining the capsule precursor for the first time in an inert atmosphere, and then heating it for the second time to obtain a graphene capsule molten salt phase change material.
2. The preparation method according to claim 1, characterized in that: The few-layer graphene oxide is prepared by the following method: Mix graphite and sulfuric acid evenly, add sodium nitrate and phosphorus pentoxide, stir at 80-100°C for 12-24h, separate and collect the solid phase, wash and shade-dry to obtain the precursor; The precursor is dispersed in excess concentrated sulfuric acid, and potassium permanganate is slowly added thereto, stirred at -10 to 0°C, and then diluted with water, and then heated to 90°C, and hydrogen peroxide is added until the solution turns bright yellow to obtain a dispersion; The dispersion is diluted with water, centrifuged at a speed of 5000-7000 r / min to remove multilayer graphene oxide, and then centrifuged at a speed of 10000-12000 r / min to remove impurities, and the concentrated solution obtained by centrifugation is freeze-dried to obtain few-layer graphene oxide.
3. The preparation method according to claim 2, characterized in that: The mass ratio of graphite, sulfuric acid, sodium nitrate and phosphorus pentoxide is (1-2):(18-20):(1.5-2):(1.5-2); The mass ratio of potassium permanganate to graphite is 5:
1.
4. The preparation method according to claim 1, characterized in that: The heating temperature is 80°C; In the slurry, the mass of the few-layer graphene oxide is 10-20 mg / mL, the concentration of polyvinyl alcohol is 120-180 mg / mL, and the concentration of sodium ascorbate is 0.3-0.8 mg / mL.
5. The preparation method according to claim 1, characterized in that: The solar salt is prepared by the following method: NaNO3 and KNO3 are mixed in a mass ratio of 6:4, ground and heated to 400°C to melt, cooled and ground again to obtain the solar salt.
6. The preparation method according to claim 1, characterized in that: The diameter of the mold is 1 to 3 cm, and the pressure applied to the mold is 10 to 15 MPa.
7. The preparation method according to claim 1, characterized in that: The freeze drying comprises: The mold is frozen by liquid nitrogen for 10 to 12 hours; then dried for 24 to 48 hours at a temperature of -70 to -80°C and a vacuum degree of <15Pa.
8. The preparation method according to claim 1, characterized in that: The temperature of the first calcination is 250-400°C; the temperature of the second calcination is 500-800°C; The inert atmosphere is an argon atmosphere.
9. The graphene capsule molten salt phase change material prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the graphene capsule molten salt phase change material prepared by the preparation method according to any one of claims 1 to 8 in an energy storage device or energy storage system.
Citation Information
Patent Citations
Molten salt / ceramic composite heat accumulator used at high temperature, and preparation method thereof
CN105349112A
Method for preparing graphene cross-linked network phase change thermal storage / conductive compositematerial
CN106190038A
Preparation method of hybrid graphene gel / phase-change heat-conducting composite material
CN106634855A
Composite phase change material and preparation method thereof
CN109554164A
Composite phase change material and preparation method thereof
CN113174237A
